2011
DOI: 10.1016/j.anorl.2011.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the status of resection margins after endoscopic laser cordectomy for T1a glottic carcinoma

Abstract: The present results show that margins considered positive after laser resection do not significantly impact carcinologic course, while still requiring close surveillance. The most generally recommended attitude is control endoscopy with biopsy at 10 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 20 publications
7
54
1
Order By: Relevance
“…Furthermore, we cannot exclude a local variation in evaluation protocol having led to this result, and finally we cannot exclude that the pathologist reviewing the samples may have been the particularly meticulous knowing that the results would be analysed for a study. Despite the high rate of positive margins, our data are in line with the literature, showing that positive margins have no impact on local control [8, 10, 11, 16]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, we cannot exclude a local variation in evaluation protocol having led to this result, and finally we cannot exclude that the pathologist reviewing the samples may have been the particularly meticulous knowing that the results would be analysed for a study. Despite the high rate of positive margins, our data are in line with the literature, showing that positive margins have no impact on local control [8, 10, 11, 16]. …”
Section: Discussionsupporting
confidence: 91%
“…However, others conclude that positive margins have no influence on local control [8, 10, 11, 16]. Therefore, the best management of close or positive margins has not been clearly determined [13] although it has been shown that mandatory retreatment could lead to unnecessary additional treatment in up to 84% of these patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…The significance of positive or close margins has been the subject of several retrospective studies with conflicting results: some studies found a significant increase in local recurrence for patients with close or positive margins 32,33 whereas others were not able to show a significant difference. 4,[34][35][36] Deep positive margins, however, after the first TLM resection contributed to lower local control and organ preservation rates for Peretti and colleagues. 4 Thus, close superficial margins may undergo complementary resection with the laser or a close watch-and-wait follow-up.…”
Section: Resection Marginsmentioning
confidence: 99%
“…As shown in Table 3, four authors chose a complete wait and see policy [6467]. Others preferred a wait and see attitude but performed several second-look procedures, on clinical indication [6870] or using the site of the positive margins (deep versus superficial) to decide whether a patient should be re-excised or not [32]. Re-treatment with either TLM or radiotherapy was standard only for three authors [7173], although not all patients were handled according to protocol, mainly because of patients’ preference.…”
Section: Factors Affecting Oncological Outcomes Of Tlmmentioning
confidence: 99%